(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
As a thinker and reformer of the period ascribed as the “Bengal Renaissance”, Swami Vivekananda is usually read and studied in the light of his impact on social andreligious reforms in India. This has elicited multiple responses to Vivekananda’s works and life ranging from profound spiriualism to political connotations. The latter again has come to be defined either in terms of eulogies for his contribution to social and political reforms during colonial rule or, much recently owing to postcolonial studies, in terms of omplicity with colonial presumptions about the Orient such as the “effeminate Bengalee”. The latter variety of critical discourse has come to closely resemble what Partha Chatterjee has aptly described as “derivative discourse”. However, my principal contention in this paper is that while the derivative nature of Vivekanada’s discourse has good enough claims to be made in its favour particularly when considered from the historical and social contexts of their formulation, its resistive potential as an anti-colonial intellectual exercise is too often missed due to a lack of serious textual engagement with them. This paper will attempt to focus on the textual aspect of Vivekanda’s thought that establishes not only its critique to the foundations of Western discourse on logic, science and politics, but also identify possible sites of subversion of these foundations in the light of Vedantic interpretation.